Icterohemoglobinuria bacilar bovina (IBB) : ultraestructura de la lesion hepatica en carneros - Garcia, M.G.=700 1 Joa, R.; Bulnes, C.; Gonzalez, A.
(Es, En)
Ilus., 12 ref.
Keywords: CARNEROS; ENFERMEDADES HEPATICAS; CLOSTRIDIUM; BACTERIA; ULTRAESTRUCTURA; REPRODUCCION; CUBA; ICTEROHEMOGLOBINURIA BACILAR BOVINA